Highly Selective and Stable Zn (II)‐Based Metal–Organic Frameworks for the Detections of Tetracycline Antibiotic and Acetone in Aqueous System. (27th April 2020) - Zhu, Bin; Zong, Ziao; Zhang, Xia; Zhang, Dongmei; Cui, Liansheng; Bi, Caifeng; Fan, Yuhua
Abstract : Tetracycline (TC) is one of the most widely used antibiotics in aquaculture, and its good water solubility makes it a major contaminant in seawater. Therefore, it is very necessary and challenging to develop an efficient detection method. In this work, two novel metal–organic frameworks [Zn (bpydb)(bimmb)0.5 ]n (1 ), [Zn2 (bpydb)2 (bimb)]·[Zn (bpydb)(bimb)]·H2 On (2 ), (bimb = 1, 4‐bis (lmidazol) butane, H2 bypdb = 4, 4′‐(4, 4'‐Bipyridine‐2, 6‐diyl)dibenzoic acid, bimmb = 1, 4‐bis (imidazol‐1‐ylmethyl)benzene) were successfully synthesized under solvothermal conditions. Zn‐MOF 1 –2 were characterized by X‐ray powder diffraction (PXRD), Fourier transform infrared (FT‐IR) spectroscopy and thermogravimetric analysis (TGA). As expected, 1 –2 have excellent fluorescence properties, thermal stability and good structural stability in water. TC in water can be detected by fluorescence quenching with high selectivity. At the same time, the fluorescence quenching efficiency remains unchanged in the presence of other interfering antibiotics and in aqueous solutions of different pH values (pH = 3–10). The detection ability of 1 in real seawater has not changed substantially, showing considerable practical application prospects. Interestingly, 1 –2 also efficiently detected traces of acetone in solution with detection limits of 0.07 μM (4.38 ppb) and 0.18 μM (10.85 ppb), respectively. In addition, the mechanism of fluorescence quenching is further discussed. Abstract : Two novel Zn‐MOFs with high chemical and thermal stability and good fluorescence properties have been designed and synthesized. They were then used to selectively detect antibiotics in water and small organic molecules in aqueous system, showing excellent fluorescence recognition performance. Based on their sensitive fluorescence quenching effect, these two Zn‐MOFs have excellent selective detection capabilities for tetracycline and acetone. In addition, the mechanism of fluorescence quenching is further discussed from electron transfer and resonance energy transfer.